Cooperativa de Produtores de Lixo: alternativas para a gestão dos resíduos domiciliares no Bairro Jardim Porto Alegre, Toledo-Pr - Gallego, Raissa Caroline (2016)
The problematic relationship between humans and nature brings out the environmental crisis which humanity passes, making frequent the social and environmental injustices. It appears that the consumption rate does not follow the speed of the return of raw materials to its natural cycle, which shows a huge disrespect to the planet we inhabit, as well as the disentanglement between the relationship Man x Nature. This is evident when we look at the amount of domiciliary solid waste destined for landfills, without considering, at least, the segregation of organic materials of inorganic. Therefore, it is urgent to rethink the management of solid waste in urban ecosystems, in a way that involves all members of society. The organization in cooperatives shows a good way of confronting a group of environmental problems, since it is configured as a space for discussion and social transformation. Thus, the present study sought to verify the contribution of the Producers Cooperative / Organic Waste and Recyclable Pickers located in Toledo-PR for the management of municipal household solid waste in Jardim Porto Alegre district. The cooperative practices recycling activities such as composting and selective collect of inorganic materials. Through analysis of documents such as the statute of the cooperative, semi-structured interviews with associates of the cooperative and its president, it was found that the actions taken have brought important benefits, such as reduction of waste going to landfill, as well as a greater level of environmental awareness. However, the use of anaerobic biodigestor to destine organic waste was inefficient, organic waste began to be destined to a composting company. Regarding the inorganic waste, they were destined to the prefecture sheds, where they were passed along to the collectors association. Both practices that the Cooperative began to perform are configured as a loss of autonomy and principles, which resulted in suspended activities for the year 2016. Thus, it is necessary that the actions that guided the activities of the Cooperative previously, are worked and thought more deeply in order to seek new means of treating solid waste, in order to perpetuate and disseminate practices that the Cooperative held.